Using Waste Concrete for Increasing Internal Sand Friction Angle - Masoud Amelsakhi; Elham Tehrani Bajgiran (مدل‌سازی پیشرفته در مهندسی عمران, 2025)
This research is a laboratory study to improve the geotechnical properties of sandy soils. Concrete waste with a grain size of 1.2 to 1 inch was used for this purpose. The effect of using concrete waste at 0, 10, 20 and 30 weight percent on dry sandy soil in two loose and dense states was investigated. Based on the results of the direct cutting test, the addition of concrete waste has increased the shear strength and the internal friction angle of the soil; The loose samples made with 30% of concrete waste had the greatest effect, so adding 30% of concrete waste to loose sand increased the internal friction angle of the soil by 32%. Similarly, adding 10% of concrete waste to dense sand increased the internal angle of friction of the soil by 4%.The obtained results show that the most positive effect in increasing the soil-waste concrete is for loose sand, especially in 30 per cent waste concrete.